Cover Feature: Undiscovered Potential: Ge Catalysts for Lactide Polymerization (Chem. Eur. J. 1/2020). Issue 1 (13th November 2019) - Rittinghaus, Ruth D.; Tremmel, Jakub; Růžička, Ales; Conrads, Christian; Albrecht, Pascal; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka N.; Pich, Andrij; Jambor, Roman; Herres‐Pawlis, Sonja
Abstract : On the expedition to replace the toxic tin catalyst for PLA production with a benign one, the high potential of germanium complexes as catalysts for industrial relevant conditions were discovered. The catalysts presented polymerize lactide in bulk at 150 °C with high efficiencies and with reaction rates of up to two magnitudes higher than the industrially used tin compound while producing long chain polymers. More information can be found in the Full Paper by R. Jambor, S. Herres‐Pawlis, et al. on page 212 .